2016
DOI: 10.1021/acs.chemmater.5b04223
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Crystal Structure During the Initial Stages of ZnO Atomic Layer Deposition

Abstract: International audienceA complementary suite of in situ synchrotron X-ray techniques is used to investigate both structural and chemical evolution during ZnO growth by atomic layer deposition. Focusing on the first 10 cycles of growth, we observe that the structure formed during the coalescence stage largely determines the overall microstructure of the film. Furthermore, by comparing ZnO growth on silicon with a native oxide with that on Al2O3(001), we find that even with lattice-mismatched substrates and low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 51 publications
5
46
1
Order By: Relevance
“…In recent years, several groups have explored extending this concept of using light to study ALD growth towards the x-ray part of the electromagnetic spectrum. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Indeed, when an ALD reactor is equipped with x-ray transparent windows (e.g., beryllium, graphite, or kapton), then the film can be (intermittently) exposed to x-rays during growth, and a wide range of x-ray based thin film characterization techniques can be used for in situ characterization, as recently reviewed by Devloo-Casier et al 17 Since ALD is typically used for nanocoatings with a thickness of 0.1 to several tens of nanometers, while xrays typically penetrate several micrometers deep into most materials, it is challenging to obtain a sufficient signal to noise ratio for x-ray based characterization techniques, in particular when targeting acquisition rates of 1-60 s in order not to interfere too much with the standard exposure cycle of the ALD process. Therefore, while lab-based x-ray sources are used routinely for ex situ analysis of, e.g., the crystallinity of ALD grown films, the in situ studies typically require the high photon flux that can only be offered by synchrotron based sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several groups have explored extending this concept of using light to study ALD growth towards the x-ray part of the electromagnetic spectrum. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Indeed, when an ALD reactor is equipped with x-ray transparent windows (e.g., beryllium, graphite, or kapton), then the film can be (intermittently) exposed to x-rays during growth, and a wide range of x-ray based thin film characterization techniques can be used for in situ characterization, as recently reviewed by Devloo-Casier et al 17 Since ALD is typically used for nanocoatings with a thickness of 0.1 to several tens of nanometers, while xrays typically penetrate several micrometers deep into most materials, it is challenging to obtain a sufficient signal to noise ratio for x-ray based characterization techniques, in particular when targeting acquisition rates of 1-60 s in order not to interfere too much with the standard exposure cycle of the ALD process. Therefore, while lab-based x-ray sources are used routinely for ex situ analysis of, e.g., the crystallinity of ALD grown films, the in situ studies typically require the high photon flux that can only be offered by synchrotron based sources.…”
Section: Introductionmentioning
confidence: 99%
“…To enable such synchrotron based experiments, a dedicated ALD setup is required that is preferably mobile so that it can be used at different beamline end stations (enabling different x-ray based characterization techniques), preferably at different synchrotron user facilities. In recent years, "in situ" setups have been developed at the National Synchrotron Light Source (NSLS I) at Brookhaven National Lab (by temporarily transforming a multi-purpose UHV chamber at beamline X21 into an ALD reactor), 10,24 at the Pohang Light Source (PLS), 14 at the Advanced Photon Source (APS) at Argonne National Laboratory, 21 at Stanford Synchrotron Radiation Lightsource (SSRL), 20 and at SOLEIL, 19,22 while "in vacuo" setups have been developed at BESSY II 25,26 and at SSRL, 27,28 mainly targeting XPS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in the literature, great attention has been given to the initial stages of growth of ZnO by thermal ALD [23][24][25][26][27][28][29][30]. Understanding the first stages of growth is of particular importance when ultrathin and continuous ZnO films are required, e.g., as an electron buffer layer for inverted solar cells [4], or as a passivation layer in transistors [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the initial growth stages, the onset of crystallinity has not received the same attention. In a series of investigations on thermal ALD ZnO, Renevier, Ciatto et al reported on the growth of ZnO when deposited on different substrates (a-SiO 2 [26][27][28], c-Al2O3 [26][27][28], In 0.53 Ga 0.47 As [29,30]). The in-situ methodology adopted (mainly X-ray based methods, such as X-ray fluorescence and X-ray absorption near-edge structure spectroscopy) identified the onset of crystallization to start from the very first cycle when deposited on c-Al 2 O 3 , adopting a 2D-like growth and developing in-plane crystallinity; a different growth behavior was instead observed when deposited on a-SiO 2 and In 0.53 Ga 0.47 As, on which the crystallinity starts after the development of an initial amorphous layer.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report on the influence of Zn precursor (diethylzinc) and oxidant (water) injection time or concentration on the ZnO initial growth stages on InGaAs. For monitoring in situ the initial stages of growth, we have implemented spectroscopic ellipsometry on our custom‐built reactor, which is used also for X‐ray studies . Provided that the appropriate model for calculating the thin‐film optical parameters is known, spectroscopic ellipsometry allows to monitor the thickness as a function of the number of cycles in situ and, most importantly, provide insights into the growth process.…”
Section: Introductionmentioning
confidence: 99%